MORPHOMETRIC ANALYSIS OF LARGER OPENINGS OF THE GREATER WING OF HUMAN SPHENOID BONE - Pavlović, Miljana; Pavlović, Miljana; Jovanović, Ivan; Trandafilović, Milena; Stojanović, Vesna; Antić, Milorad; Čukuranović Kokoris, Jovana; Stanković, Milica (Acta medicae Medianae, 2021)
Analysis of the anatomical characteristics of openings of the greater wing of the sphenoid bone (round, oval and spinous opening – FR, FO and FS) has clinical significance in surgical and diagnostic procedures. The aim of the study was to examine the morphological and morphometric characteristics of the round, oval and spinous openings on human skulls. The research was conducted on 20 skulls of the Institute of Anatomy of the Faculty of Medicine in Niš. The skulls were numerated, and the openings were photographed beside the ruler with a Canon A470 camera. Photo processing and morphometric analysis (measuring the length and width of the FR, FO and FS) were performed in the program "ImageJ". The average length of the FR right was 3.14±0.77 mm, left 3.44±0.65 mm, width right 2.38±0.58 mm, left 2.61±0.55 mm; length of the FO right 5.88±0.88 mm, left 5.50±1.06 mm, width right 2.70±0.58 mm, left 2.82±0.68 mm; length of the FS right 1.65±0.27 mm, left 1.73±0.49 mm, width right 1.32±0.32 mm, left 1.20±0.39 mm. T-test of independent samples determined no statistically significant difference between the parameters on both sides, nor between the measured parameters on the same openings. A mean positive correlation exists between FS length and width on the left, FR length and width on the right and between FS widths on both sides; a negligible positive correlation between the length and width of FO on the right and between lengths of the FS on both sides; a weak positive correlation exists between other measured parameters.
Keywords: round opening, oval opening, spinous opening, greater wing of the sphenoid bone